Cellulose fibres as a reinforcing element in building materials - Hospodarova, Viola; Stevulova, Nadezda; Vaclavik, Vojtech; Dvorsky, Tomas; Briancin, Jaroslav (International Conference “Environmental Engineering”, 2017)
Nowadays, construction sector is focusing in developing sustainable, green and eco-friendly building materials. Natural fibre is growingly being used in composite materials. This paper provides utilization of cellulose fibres as reinforcing agent into cement composites/plasters. Provided cellulosic fibres coming from various sources as bleached wood pulp and recycled waste paper fibres. Differences between cellulosic fibres are given by their physical characterization, chemical composition and SEM micrographs. Physical and mechanical properties of fibre-cement composites with fibre contents 0.2; 0.3and 0.5% by weight of filler and binder were investigated. Reference sample without fibres was also produced. The aim of this work is to investigate the effects of cellulose fibres on the final properties (density, water absorbability, coefficient of thermal conductivity and compressive strength) of the fibrecement plasters after 28 days of hardening. Testing of plasters with varying amount of cellulose fibres (0.2, 0.3 and 0.5 wt. %) has shown that the resulting physical and mechanical properties depend on the amount, the nature and structure of the used fibres. Linear dependences of compressive strength and thermal conductivity on density for plasters with cellulosic fibres adding were observed.